2021
DOI: 10.1021/acs.est.1c01200
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Characterization of Human Serum Albumin Binding for Per- and Polyfluoroalkyl Substances Using Differential Scanning Fluorimetry

Abstract: Per- and polyfluoroalkyl substances (PFAS) are a diverse class of synthetic chemicals that accumulate in the environment. Many proteins, including the primary human serum transport protein albumin (HSA), bind PFAS. The predictive power of physiologically based pharmacokinetic modeling approaches is currently limited by a lack of experimental data defining albumin-binding properties for most PFAS. A novel thermal denaturation assay was optimized to evaluate changes in the thermal stability of HSA in the presenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 45 publications
8
38
0
Order By: Relevance
“… Greaves et al (2013) also reported a positive correlation between longer chain perfluorinated carboxylic acids (PFCAs) and extractable lipid content in the brainstem and cerebellum, hypothesizing that PFCAs with carbon chain lengths between 10 and 15 may be binding to serum proteins and crossing the BBB in a similar way to saturated fatty acids. This hypothesis is supported by in vitro work demonstrating that proteins like human serum albumin and human L-FABP have optimal affinity for PFAS with carbon chain length around 10 ( Zhang et al, 2013 ; Jackson et al, 2021 ).…”
Section: Pfas Uptake and Accumulation In The Brainmentioning
confidence: 84%
See 2 more Smart Citations
“… Greaves et al (2013) also reported a positive correlation between longer chain perfluorinated carboxylic acids (PFCAs) and extractable lipid content in the brainstem and cerebellum, hypothesizing that PFCAs with carbon chain lengths between 10 and 15 may be binding to serum proteins and crossing the BBB in a similar way to saturated fatty acids. This hypothesis is supported by in vitro work demonstrating that proteins like human serum albumin and human L-FABP have optimal affinity for PFAS with carbon chain length around 10 ( Zhang et al, 2013 ; Jackson et al, 2021 ).…”
Section: Pfas Uptake and Accumulation In The Brainmentioning
confidence: 84%
“…As the brain is most susceptible to penetration by lipophilic compounds, there is cause for concern that some PFAS may elicit considerable neurotoxic effects. In addition, the blood is one of the major compartments in which PFAS partitions, due to the relatively low affinity binding of PFAS to serum albumin ( Maestri et al, 2006 ; Kudo et al, 2007 ; Bogdanska et al, 2011 ; Jackson et al, 2021 ; Robuck et al, 2021 ). Thus, due to the highly vascularized nature of the brain, there is enhanced risk of brain exposure to toxicants found in the blood, including PFAS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PFAS efficiently bind to serum albumin 40 and albumin is a major carrier for PFOS, PFOA, PFNA, PFDA, and PFHxS, in human plasma 41 . PFAS binding to albumin is a critical mediator of PFAS distribution in different organ systems 41,42 .…”
Section: Introductionmentioning
confidence: 99%
“…2 of the European Chemicals Risk Assessment Committee Agency), and it has a residence time of 3.8 years in human blood and breastmilk [10]. These compounds are well absorbed orally, poorly eliminated and distributed in a tissue-dependent manner, due to their high binding affinity to serum albumin and fatty acid-binding proteins, mainly in serum, kidney and liver [11,12]. In humans, detectable levels of PFOS and PFOA have been reported in blood [8], in the umbilical cord, and in many organs [13,14], where levels may vary due to various factors [3].…”
Section: Introductionmentioning
confidence: 99%